Role of Corin in Trophoblast Invasion and Uterine Spiral Artery Remodeling in Pregnancy - Cui, Yujie (2012)
In pregnancy, trophoblast invasion and uterine spiral artery remodeling are important for lowering maternal vascular resistance and increasing uteroplacental blood flow. Impaired spiral artery remodeling has long been implicated in preeclampsia, a major complication of pregnancy, but the underlying mechanisms remain unclear(1, 2). Corin is a cardiac protease that activates atrial natriuretic peptide (ANP), a cardiac hormone important in regulating blood pressure(3). Unexpectedly, corin expression was detected in the pregnant uterus(4). Here we identify a novel function of corin and ANP in promoting trophoblast invasion and spiral artery remodeling. We show that pregnant corin- or ANP-deficient mice developed high blood pressure and proteinuria, characteristics of preeclampsia. In these mice, trophoblast invasion and uterine spiral artery remodeling were markedly impaired. Consistently, we find that ANP potently stimulated human trophoblasts in invading Matrigels. In patients with preeclampsia, uterine corin mRNA and protein levels were significantly lower than that in normal pregnancies. Moreover, we have identified corin gene mutations in preeclamptic patients, which decreased corin activity in processing pro-ANP. These results indicate that corin and ANP are essential for physiological changes at the maternal-fetal interface, suggesting that defects in corin and ANP function may contribute to preeclampsia.